Elaboração de tabela de aminas bioativas em alimentos e estimativa da ingestão no Brasil - Fabiana Barbosa Diniz (2015)
The objectives of this work were to develop a food composition data base with the levels of ten bioactive amines, to identify foods with expressive levels of polyamines, histamine and pressor amines, and to estimate the ingestion of these amines in different regions of Brazil. To create the food data base on amines, the scientific literature was searched using as criteria a minimum of five samples of a food and results of analysis by high performance liquid chromatography. The database, called TAMIN comprised of a total of 242 food items categorized into 17 food groups (fruits, vegetables, mushrooms, cereals and grains, pulses, oilseeds, starches, meat and meat products, fish, eggs, milk and dairy products, infant formula and human milk, beverages, alcoholic drinks, oils, enteral formula and miscellaneous. The food items with expressive levels of polyamines (spermine + spermidine), of histamine and of pressor amines (tyramine, tryptamine and phenylethylamine) were described. The foods with expressive levels of polyamines were: beef and chicken liver, soybean, sorghum, soy protein isolate, cowpea, grated parmesan cheese, corn, mushroom (black shimeji, salmon) and passion fruit. The foods with expressive levels of histamine were: grated cheese, soy sauce, eggplant (skin). The foods with expressive levels of pressor amines were: grated cheese, sausage (brianza, friolano, italiano, hamburgues and milano) and eggplant (skin). The per capita ingestion of these amines in the different Brazilian regions were estimated using IBGEs Program of Household Budget (POF) and the levels of amines from TAMIN. The per capita ingestion of polyamines varied from 11.26 to 17.03 mg/day, respectively in the Southern and Northeastern regions. The highest ingestion of histamine was estimated on the Northern region (4 mg/day), and the smallest in the Southern (1.31 mg/day) region of Brazil. The ingestion of pressor amines was the highest in the Midwest (2.03 mg/day) and the smallest in the North of Brazil (1.62 mg/day).